Nitrite toxicity in Aspergillus nidulans: Effect of mutation at the nihB gene - Pombeiro, S. R C [UNESP]; Rossi, A.; Martinez-Rossi, N. M. (Springer Nature, 1992)
The nihB gene of Aspergillus nidulans was found to confer sensitivity to elevated concentrations of nitrite, compact morphology and absence of conidiation. The nihB locus was allocated to linkage group II and was recessive in heterozygous diploids. When the nihB1 mutant was grown on a mixture of nitrite plus NH4 + its sensitivity to nitrite was unchanged. A possible role for this gene in nitrite transport and/or the maintenance of membrane integrity is discussed. © 1992 Rapid Communications of Oxford Ltd.
Keywords: Aspergillus nidulans; conidiation; nitrite; nitrogen source